Altered Tim-1 and IL-10 Expression in Regulatory B Cell Subsets in Type 1 Diabetes - Liu, Yikai; Chen, Zhiying; Qiu, Junlin; Chen, Hongzhi; Zhou, Zhiguang (Frontiers in Immunology, 2021)
Background Type 1 diabetes (T1D) is an autoimmune disease with a complex aetiology. B cells play an important role in the pathogenesis of T1D. Regulatory B cells (Bregs) are a subset of B cells that produce and secrete the inhibitory factor interleukin-10 (IL-10), thereby exerting an anti-inflammatory effect. It was recently discovered that T-cell immunoglobulin mucin domain 1 (Tim-1) is essential for maintaining Bregs function related to immune tolerance. However, the detailed understanding of Tim-1+ Bregs and IL-10+ Bregs in T1D patients is lacking. This study aimed to characterize the profile of B cell subsets in T1D patients compared with that in controls and determine whether Tim-1+ Bregs and IL-10+ Bregs play roles in T1D. Materials and Methods A total of 47 patients with T1D, 30 patients with type 2 diabetes (T2D) and 24 healthy controls were recruited in this study. Flow cytometry was used to measure the levels of different B cell subsets (including B cells, plasmablasts, and Bregs) in the peripheral blood. Radiobinding assays were performed to detect the antibody titres of T1D patients. In addition, the correlations between different B cell subsets and patient parameters were investigated. Results Compared with healthy controls, differences in frequency of Tim-1+ Bregs were significantly decreased in patients with T1D (36.53 ± 6.51 vs. 42.25 ± 6.83, P=0.02*), and frequency of IL-10+ Bregs were lower than healthy controls (17.64 ± 7.21vs. 24.52 ± 11.69, P=0.009**), the frequency of total Bregs in PBMC was also decreased in patients with T1D (1.42 ± 0.53vs. 1.99 ± 0.93, P=0.002.**). We analyzed whether these alterations in B cells subsets were associated with clinical features. The frequencies of Tim-1+ Bregs and IL-10+ Bregs were negatively related to fasting blood glucose (FBG) (r=-0.25 and -0.22; P=0.01* and 0.03*, respectively). The frequencies of Tim-1+ Bregs and IL-10+ Bregs are positively correlated with fast C-peptide (FCP) (r=0.23 and 0.37; P=0.02* and 0.0001***, respectively). In addition, the frequency of IL-10+ Breg was also negatively related to glycosylated haemoglobin (HbA1c) (r=-0.20, P=0.04*). The frequencies of Tim-1+ Bregs, IL-10+ Bregs and Bregs in T2D patients were reduced, but no statistically significant difference was found between other groups. Interestingly, there was positive correlation between the frequencies of Tim-1+ Bregs and IL-10+ Bregs in T1D (r=0.37, P=0.01*). Of note, it is worth noting that our study did not observe any correlations between B cell subsets and autoantibody titres. Conclusions Our study showed altered Tim-1 and IL-10 expression in regulatory B cell in T1D patients. Tim-1, as suggested by the present study, is associated with islet function and blood glucose levels. These findings indicate that Tim-1+ Bregs and IL-10+ Bregs were involved in the pathogenesis of T1D.